Equi-intensity across the Spectrum™ taste scales. (September 2015) - Martin, Christophe; Maire, Aurélia; Chabanet, Claire; Issanchou, Sylvie
Highlights: This work aimed to study the equi-intensity across the Spectrum™ taste scales. The five basic tastes were studied. The scales were compared using two methods: 2-AFC and LMS. Equi-intensity property was not observed for all tastes and all levels of intensity. Estimation models allowing calculation of equi-intense sapid solutions were provided. Abstract: This work aimed to study the equi-intensity across the Spectrum™ taste scales. The approach consisted of a comparison of four reference points illustrating the same level of intensity across the scales using two very different methods: 2-alternative forced-choice (2-AFC) and Labeled Magnitude Scale (LMS). The comparisons across these scales were based on caffeine, citric acid, sodium chloride, sucrose, and monosodium glutamate in water solutions, at different concentrations, prepared according to the guidelines given for the Spectrum™ method. A scale concerning the umami taste, designed in the spirit of the Spectrum™ scales, was also studied in this work. Both procedures produced similar outcomes, which is very powerful for the overall validity of the study. The results show that the equi-intensity property was not observed for all tastes and all levels of intensity. The most important differences across scales were observed for scores above the midpoint on the scales. The results of this study suggest that it would be necessary to modify the concentrations of several of the reference solutions assigned to the reference points given in the guidelines of the Spectrum™ method. This work also provided estimation models allowing calculation of equi-intense sucrose, caffeine, NaCl, citric acid and MSG water solutions.